Graduate Education in Malaysia and Thailand - Chien, Chiao-Ling; Chapman, David W (International Higher Education, 2014)
Graduate education in Malaysia and Thailand has expanded significantly to provide qualified instructors to serve growing undergraduate enrollment. In both countries, this rationale was eclipsed, to a large extent, by the view that graduate education would help fuel national economic development. The focus on economic development triggered an intensified emphasis on universities placing high in international rankings which, in turn, led to pressure for more research.